Lip Print Analysis to Predict Type 2 Diabetes Mellitus and Ethnicity Identification among Saudi and Kuwaiti Population - Nishath Sayed Abdul; Fatma Hassan Al Quraini; Shammaa Alquraini; Reema Al Khaldi; Al Jouhara Nahar Al Saud (Journal of Pharmacy and Bioallied Sciences)
Background: Lip prints, or cheiloscopy, have potential forensic and diagnostic applications. The present study was undertaken to assess the correlation between lip print patterns and type 2 diabetes mellitus (T2DM) in Saudi and Kuwaiti female populations, as well as explore ethnic differences in lip print patterns. Methods: A descriptive study was performed among 121 female participants (30 diabetics and 91 non-diabetics) aged 20–65 years from Saudi Arabia and Kuwait. Cheiloscopic patterns were analyzed using the Tsuchihashi and Suzuki categorization. Data analysis was done using the Chi-square test of association. For all analysis, level of significance was set below 5%. Results: Saudi diabetic females predominantly exhibited the vertical lip print pattern (67%), while the reticular pattern (73%) was most common in Kuwaiti diabetics. Non-diabetic participants in both groups primarily showed the undifferentiated pattern. Significant differences were found between diabetic Saudi and Kuwaiti females. The branched pattern (16.1%) in non-diabetic Saudis may indicate future risk for T2DM. Conclusion: Lip print analysis shows potential as a non-invasive marker for T2DM risk and ethnic differentiation. Further studies are needed to confirm its utility as a diagnostic tool.